Peningkatan Kemampuan Mengenal Lambang Bilangan 1-10 Melalui Penggunaan Media Buah Puzzle Angka Pada Kelompok A Di Raudlatul Athfal Babussalam, Krian, Sidoarjo - Alfiatul Izzati Irawan (JECED : Journal of Early Childhood Education and Development, 2019)
This research was motivated by the ability to recognize symbols number 1-10 at low Raudlatul Athfal Babussalam. This is evidenced by student learning outcomes that show 78.26% of children do not know the symbol number 1-10 in the age range 4-5 years. This study aims to determine the learning process of recognizing the symbol numbers 1-10 in Group A at Raudlatul Athfal Babussalam, Krian, Sidoarjo by using Puzzle number media. As well as to find out the ability to recognize the symbol numbers 1-10 in Group A at Raudlatul Athfal Babussalam, Krian, Sidoarjo through the use of Puzzle numbers. The method used in this study is classroom action research with Kurt Lewin's model. This research was from Pre Cycle, Cycle I, Cycle II, and Cycle III. In Cycle I, Cycle II, and Cycle III consists of four stages, namely planning, action, observation, and reflection. The subjects of this study were students of Raudlatul Athfal Group A1 Age 4-5 years with 23 children. The research results are as follows: 1) Learning by using Puzzle fruit media numbers can run well in each cycle. This can be seen from the observations of teacher and student activities. The results of teacher activity in the first cycle reached 78.6%, (enough) 83.4% cycle II (sufficient), and 92.8% (good) cycle III. While the results of observations of student activities in the first cycle reached 76.2% (enough), cycle II 83.4% (enough), and cycle III 94.04% (very good). 2) There is an increase in the ability to recognize the symbol number 1-10 after the use of media numbers Puzzle numbers. This can be seen from the results of children's learning completeness at the first cycle stage 39.2% (Not Developed) with an average of 50.35 (enough), cycle II results of 60.9% (Starting to Grow) with the average learning outcomes of children 68.09 (enough), and cycle III results of 91.4% of children's learning outcomes (Very Good Developing) with an average of 82.9 (good). The increase in cycle III occurs when the use of fruit puzzle media is accompanied by singing method while writing numbers. Children will get the experience of writing numbers concretely through the song "numbers". So that in this case the child memorizes the form from the symbol number 1 to 10